2006
DOI: 10.2202/1542-0485.1150
|View full text |Cite
|
Sign up to set email alerts
|

Market Segmentation Analysis of Preferences for GM Derived Animal Foods in the UK

Abstract: This paper undertakes a detailed market segmentation analysis of the demand for GM derived animal foods in the UK with the aim of illustrating how this analysis can provide distinct information that can assists in evaluating the welfare impacts of proposed changes to the EU's GM labelling policy. The specific modelling approach employed was the latent segment (LS) model which allows for the simultaneous determination and explanation of both segment membership and product choice. Based on psychometric and demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 1 publication
2
38
1
3
Order By: Relevance
“…Full details on the specification of the LCM approach can be found in, for example, work by Hynes et al [2008]. An alternative method for modeling unobserved heterogeneity is the random parameter logit (RPL) model which allows model parameters to vary randomly over individuals, and assumes that each individual represents a segment [Train, 1998;Kontoleon and Yabe, 2006]. In other words the LCM is a special case of the RPL model, where the random coefficient is discretely distributed, i.e., there are finite number of segments, in contrast to a RPL model where the coefficient has a continuous distribution.…”
Section: Choice Experiments Methods and Latent Class Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details on the specification of the LCM approach can be found in, for example, work by Hynes et al [2008]. An alternative method for modeling unobserved heterogeneity is the random parameter logit (RPL) model which allows model parameters to vary randomly over individuals, and assumes that each individual represents a segment [Train, 1998;Kontoleon and Yabe, 2006]. In other words the LCM is a special case of the RPL model, where the random coefficient is discretely distributed, i.e., there are finite number of segments, in contrast to a RPL model where the coefficient has a continuous distribution.…”
Section: Choice Experiments Methods and Latent Class Modelsmentioning
confidence: 99%
“…Scarpa et al [2005] applied this method to study preferences over water services attributes. Hu et al [2004] and Kontoleon and Yabe [2006] used the LCM to investigate consumers' preferences for food attributes. Aldrich et al [2007] estimated the heterogeneity over public's preferences for endangered species using LCM.…”
Section: Previous Literaturementioning
confidence: 99%
“…While several studies conclude that socio-demographic variables (alone) do not have a strong explanatory power to predict acceptance of GM food products (Bredahl et al, 1998;Baker and Burnham, 2001;Kontoleon and Yabe, 2006;Anand et al, 2007), other studies found several socio-demographic differences in GM food acceptance (Hoban, 1998;Chen and Li, 2007). For example, women Moerbeek and Casimir, 2005), older people (Ganiere et al, 2006) and those with a low education (Hoban, 1998;Traill et al, 2004) or a low income level (Wachenheim et al, 2008;Yee et al, 2008) are generally more skeptical of GM food.…”
Section: Determinants Of Gm Food Acceptancementioning
confidence: 99%
“…GM derived animal foods UK 1 -Opponents (7.6 %) 2 -Cautious (41.3 %) 3 -Optimists (51.1 %) (Kontoleon and Yabe, 2006) GM maize South Africa 1 -Anti-GM, brand aware (35 %) 2 -Brand unaware, farmer sympathetic (20 %) 3 -GM consumer benefit, brand aware (25 %) 4 -Brand aware, Pro-GM (20 %) (Vermeulen et al, 2005) GM oil seed a Australia 1 -Conservatives (28 %) 2 -Confident protectors (51 %) 3 -Anti-GM (20 %) (Cox et al, 2008) GM tofu Taiwan 1 -Conventional Buyer (45 %) 2 -GMO Buyer (32 %) 3 -Non-GMO buyer (23 %) (Jan et al, 2007) Note: c = chocolate; t = tomato a To our knowledge these are the only segmentation studies solely focusing on GM products with consumer benefits, the socalled 2 nd generation GM products; b 4 th , 5 th , 6 th and 7 th Eurobarometer Surveys are conducted in 1999, 2002, 2005 and 2010, respectively; c In the 5 th Eurobarometer 'undecided' is replaced by 'risk-tolerant'; d Although the authors discovered three additional, smaller segments with respect to GM tomatoes, only the common clusters are shown.…”
Section: Product Category Location Identified Clusters (% Respondentsmentioning
confidence: 99%
See 1 more Smart Citation